2022
DOI: 10.1111/cfs.12922
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated adulthood, extended adolescence and the care cliff: Supporting care leavers' transition from care to independent living

Abstract: The pressures of 'accelerated adulthood' are a critical challenge for young people ageing out of the care system. Despite the trauma related to their placement history, young people 'aging out' are expected to adapt to adulthood at younger age and faster pace than their non-care peers, who enjoy an 'extended adolescence' a far more gradual progression into adulthood than previous generations. This article draws on firstperson narratives of care leavers in Ireland who have aged out of care and transitioned into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Similarly, Frontline (2022) offers a two-year training programme to fully equip individuals with the knowledge and experience needed to effectively support care leavers. The need for additional training programmes is supported by research (Sulimani‐Aidan et al , 2021; Palmer et al , 2022), who discovered the importance of effective professional support during the transition period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Frontline (2022) offers a two-year training programme to fully equip individuals with the knowledge and experience needed to effectively support care leavers. The need for additional training programmes is supported by research (Sulimani‐Aidan et al , 2021; Palmer et al , 2022), who discovered the importance of effective professional support during the transition period.…”
Section: Resultsmentioning
confidence: 99%
“…Butterworth et al (2017) suggested the consensus among participants was that there was a lack of understanding between professionals' knowledge of mental health and a lack of specialised knowledge of children in care and care leavers when it came to the mental health services. Palmer et al, 2022), who discovered the importance of effective professional support during the transition period.…”
Section: Training Given To Care Professionals and Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…Broadly, individuals with alternative care experience tend to have poorer outcomes in adulthood. They have higher rates of criminal activity, unemployment, homelessness and poverty (Berejena Mhongera & Lombard, 2016; Diraditsile & Nyadza, 2018; Palmer et al, 2022; Sekibo, 2020; Sulimani‐Aidan, 2017). Adults who experienced alternative care as children are more likely to attempt suicide and abuse substances (Berlin et al, 2011), have lower life satisfaction and subjective well‐being (Llosada‐Gistau et al, 2015; Pound & Sims‐Schouten, 2022; Refaeli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biological parents, these youth are often separated from their siblings, friends, and communities of origin [ 16 ]. Young adults who experienced separation from parental care during childhood are more likely to experience negative outcomes in adulthood including a higher risk of self-harm [ 17 ], violent criminal behavior [ 18 ], and homelessness [ 19 ]. Previous studies have also shown evidence of poor mental health, lower life satisfaction, insecure attachment, and less resilience among young adults with care experience due to their limited social connections [ 12 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%